A importância do estudo sobre os estrangeirismos lexicais na sala de aula: uma análise a partir de textos publicitários - Fabiana Kelly de Souza (2013)
The lexical loanwords are a current and productive way of increasing lexical competence in language. Based on this assumption, we believe that the study of loanwords in the classroom can provide students a way to understand these words and how they relate to the language. The use of foreign words in texts of a wide circulation justifies their study in the classroom, because it means that these words are shared and accepted by the linguistic community. Moreover, such texts are not only intended for people who master a foreign language, but to the general public. In this research, we undertook an analysis, from a pedagogical perspective, of lexical loanwords found in written advertising, trying to demonstrate some ways to work these units in the classroom. For this purpose, we chose as corpus analysis publicity texts conveyed in Veja magazine, from January 2009 to January 2010, which contained lexical loanwords. We analyze these units found in relation to their type and context of occurrence. We reached the conclusion that the units fou nd were divided into two groups: the stylistic loanwords, the units used to create a gap in the text and therefore they are very specific occurrences and denominative loanwords; the units mainly used to name new elements in the language and that therefore are most common. We established, from this division, two criteria for the exploration of such loanwords in the classroom. The words classified in the first criteria were approached within the context of origin and were involved in approaches in which were focused the lexical choices and their importance within the text. Those belonging to the second criterion were also worked within the context of origin; however, these words were explored with an emphasis on general purpose.